2020
DOI: 10.26434/chemrxiv.13302098
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Isomerization and Fragmentation Reactions on the [C2SH4] Potential Energy Surface. The Metastable Thione-S-Methylide Isomer

Abstract: Thione S-methylide (TSM), the parent species of the thiocarbonyl ylide family, is a 1,3-dipolar, planar species on the [C2SH4] potential energy surface (PES), which has not shared the richness of studies dedicated to its isomers, the cyclic thiirane (THI), and the keto-enol pair vinyl thiol (VTH)/thioacetaldehyde (THA). While the conrotatory ring closure reaction toward THI was studied in the ‘90s, no complete analysis of the PES is available in the literature. In the present paper, we report a computational s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…In passing, it should be noted that the previous LRA parameterization for the B3LYP and B2PLYP functionals was performed by using the SNSD and cc-pVTZ basis sets, respectively, whereas recent investigations have pointed out the necessity of augmenting the basis set with an additional set of d functions for the S atom (and in general for second-row elements) in order to improve the predictions of structural, spectroscopic, 22 and thermochemical properties. 8,76,77 The CS distance is systematically overestimated at the rev-DSDBPEP86/jun-cc-pV(D+d)Z level of theory by about 0.004 Å, with a maximum error of 0.009 Å, whereas CCS, CSC, and SCH angles are predicted with a remarkable accuracy, with the MADs being 0.09, 0.08, and 0.16°, respectively; thus, they require only minor adjustments. The LRA parameterization for the CS bond length reduces the MAD to 0.0012 Å, and it narrows the errors from the corresponding SE equilibrium values to the range of −0.003 to 0.003 Å.…”
Section: Resultsmentioning
confidence: 96%
“…In passing, it should be noted that the previous LRA parameterization for the B3LYP and B2PLYP functionals was performed by using the SNSD and cc-pVTZ basis sets, respectively, whereas recent investigations have pointed out the necessity of augmenting the basis set with an additional set of d functions for the S atom (and in general for second-row elements) in order to improve the predictions of structural, spectroscopic, 22 and thermochemical properties. 8,76,77 The CS distance is systematically overestimated at the rev-DSDBPEP86/jun-cc-pV(D+d)Z level of theory by about 0.004 Å, with a maximum error of 0.009 Å, whereas CCS, CSC, and SCH angles are predicted with a remarkable accuracy, with the MADs being 0.09, 0.08, and 0.16°, respectively; thus, they require only minor adjustments. The LRA parameterization for the CS bond length reduces the MAD to 0.0012 Å, and it narrows the errors from the corresponding SE equilibrium values to the range of −0.003 to 0.003 Å.…”
Section: Resultsmentioning
confidence: 96%
“…Previous works have shown that both methods are equivalent in a number of situations. 66,67 Required geometry optimizations at the DFT level were performed with very tight criteria. Analytical frequency calculations were performed using the DFT methods, and the thermochemical properties calculated using the rigid− rotor/harmonic oscillator approximation.…”
Section: Chemical Models and Methodsmentioning
confidence: 99%